2023
DOI: 10.1108/ajems-11-2022-0444
|View full text |Cite
|
Sign up to set email alerts
|

Foreign bank presence and inclusive growth in Africa: the moderating role of financial development

Khadijah Iddrisu,
Joshua Yindenaba Abor,
Thadious Kannyiri Banyen

Abstract: PurposeThe purpose of this study is to assess the extent to which the nexus between foreign bank presence (FBP) and inclusive growth is being impacted by the financial development.Design/methodology/approachThe study used a two-stage system generalized method of moment (GMM), using 28 African countries from the period 2000 to 2018.FindingsThe study found a positive effect of FBP on inclusive growth. While financial development magnifies the positive effect of FBP, inclusive growth nexus, it has a direct effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
(140 reference statements)
0
0
0
Order By: Relevance
“…Starting with objective one, Table 4 shows that FBP reduces income inequality in Africa with a significant coefficient of 0.0055 at 1% significant level (see column 1). The negative effect implies that FBP can enrich local banking expertise, attracting skilled professionals and disseminating knowledge, thereby enhancing access to innovative financial services for marginalised groups [53,71]. The negative effect of FBP can also be attributed to the ability of foreign banks to stimulate competition in the banking sector of the host countries [17].…”
Section: System Gmm Results Of Fbp Economic Freedom and Income Inequa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Starting with objective one, Table 4 shows that FBP reduces income inequality in Africa with a significant coefficient of 0.0055 at 1% significant level (see column 1). The negative effect implies that FBP can enrich local banking expertise, attracting skilled professionals and disseminating knowledge, thereby enhancing access to innovative financial services for marginalised groups [53,71]. The negative effect of FBP can also be attributed to the ability of foreign banks to stimulate competition in the banking sector of the host countries [17].…”
Section: System Gmm Results Of Fbp Economic Freedom and Income Inequa...mentioning
confidence: 99%
“…Nanivazo et al [16] found that FBP leads to poverty in Africa and hence concluded that FBP is associated with a higher income gap. Iddrisu et al [53] also found that in Africa, FBP advances inclusive growth, especially in the presence of a developed financial sector. One of the current studies made a significant contribution to FBP-income inequality nexus (see [20]).…”
Section: Empirical Reviewmentioning
confidence: 94%